Ankle‐Brachial Index and Cardiovascular Mortality in Nondiabetic Hemodialysis Patients. Issue 4 (11th August 2013) - Bevc, Sebastjan; Purg, Darinka; Turnšek, Nina; Hren, Martin; Hojs, Nina; Zorman, Tadej; Pečovnik‐Balon, Breda; Dvoršak, Benjamin; Ekart, Robert; Hojs, Radovan
Abstract Atherosclerosis is a leading cause of morbidity and mortality in hemodialysis (HD) patients. Low (<0.90) and high (>1.40) ankle‐brachial index (ABI) is known as a non‐invasive diagnostic marker for generalized atherosclerosis associated with higher cardiovascular (CV) mortality in the general population. Less is known about associations between ABI and CV mortality in HD patients. The aim of our study was to determine the impact of the ABI on CV mortality in nondiabetic HD patients. Fifty‐two nondiabetic HD patients (mean age 59 years, range 22 – 76 years) were enrolled in our study. Twenty‐three (44%) were women and 29 (56%) men. The ABI was determined using an automated, non‐invasive, waveform analysis device. All patients were divided according to the ABI into three groups: low ABI (<0.9), normal ABI (0.9–1.4) and high ABI (>1.4). The presence of arterial hypertension and smoking was established. Serum cholesterol (HDL and LDL) and triglycerides were measured by routine laboratory methods. Survival rates were analyzed using Kaplan–Meier survival curves. The Cox regression model was used to assess the influence of the ABI on CV outcomes. The model was adjusted for age, arterial hypertension, smoking, cholesterol and triglycerides. Mean ABI value was 1.2 ± 0.3 (range 0.2–2.2). Patients were observed from the date of the ABI measurement until their death or maximally up to 1620 days. Kaplan–Meier survival analysis showed that the risk for CV death was higher for HD patients with low and high ABI compared to normal ABI (log rank test: P < 0.006; P < 0.0001). In the adjusted Cox multivariable regression model low and high ABI (P < 0.011; P < 0.003) remained predictors of mortality in our patients. The results indicate a U‐shaped association between the ABI and CV mortality in nondiabetic HD patients and showed that low and high ABI were directly associated with higher mortality of our patients.